Long non-coding RNA AC133552.2: biomarker and therapeutic target in osteosarcoma via PANoptosis gene screening - Wenrui Zhao; Yameng Wang; Junchao Zhu; Shahrzad Arya; Guowen Huang; Shengqin Li; Qi Chen; Xijuan Liu; Jinghong Yuan; Jingyu Jia (Scientific Reports)
Abstract Osteosarcoma, the most common primary bone cancer in children and adolescents, presents significant challenges, particularly in metastasis and recurrence, resulting in poor survival rates. This study explores the role of PANoptosis—a complex cell death mechanism involving pyroptosis, apoptosis, and necroptosis—in osteosarcoma by identifying relevant long non-coding RNAs (lncRNAs) and their prognostic significance. Bioinformatics analyses used RNA expression data from the GEO and TARGET databases to identify differentially expressed genes (DEGs) and PANoptosis-related genes (PRGs). Co-expression analysis revealed lncRNAs linked to PRGs, forming a risk prognostic model. Five PRGs and two lncRNAs were significantly associated with prognosis, with the model showing high predictive accuracy (AUC 0.876, 0.787, and 0.794 for 1, 3, and 5 years). Notably, lncRNA AC133552.2 was downregulated in osteosarcoma tissues, correlating with poor survival and reduced immune infiltration. Silencing AC133552.2 promoted cell proliferation and migration, while overexpression inhibited tumor growth and metastasis, confirmed in xenograft models. AC133552.2 emerges as a potential biomarker and therapeutic target, with future research needed to explore its molecular mechanisms and clinical application.